2010
DOI: 10.7322/abcs.v35i3.80
|View full text |Cite
|
Sign up to set email alerts
|

The ethical issues of research involving human beings contained in the editorial guidelines of Brazilian medical journals

Abstract: The present study aimed to analyze the ethical aspects contained in the sections “Instructions to authors” of Brazilian medical journals which were highly qualified on the assessment of the Qualis program of Conselho Técnico Científico da Educação Superior (CTC-ES) (Medicine I area - reference year 2007). Moreover, we searched in the journals that present information about the ethical issues involved in research with humans, if these journals inform the authors about how they should confirm to the editors the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Studies have shown a tenuous participation of Brazilian journals in fulfilling the ethical aspects of human research, although more recently an improvement has been perceived 11,19,20,23,26,30,31,33 . The journals can contribute to the fulfillment of ethical issues by publishing only studies that satisfy the bioethical standards.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown a tenuous participation of Brazilian journals in fulfilling the ethical aspects of human research, although more recently an improvement has been perceived 11,19,20,23,26,30,31,33 . The journals can contribute to the fulfillment of ethical issues by publishing only studies that satisfy the bioethical standards.…”
Section: Introductionmentioning
confidence: 99%